La Incidencia de la educación financiera en las finanzas personales de los estudiantes de posgrado de la UPTC de Tunja (2023)
Eng: Financial education allows the population to know about the entities that surround them, to understand about the elementary events that can lead a country or person to a crisis, to know how financial entities work and what is the role of the citizen in the administration of funds, to understand figures, graphs and elementary research on the economy and finances; the university as a key actor in the formation of competent professional leaders has an indispensable and inalienable role in financial education; students as next, professionals and consumers of the future will be the main incentivizers of the economy of the community and the world. With these premises, the following objective is proposed: To evaluate the level of financial education in personal finances and the factors to take into account in the financial decision making of graduate students of the UPTC of Tunja. For the resolution of this purpose a questionnaire is developed, validated by means of a reliability assessment calculated by Cronbach's Alpha, therefore, with the qualitative methodology of fsQCA seeks to logically satisfy diverse applicative hypotheses, by means of Artificial Intelligence simulations. The study in general determines that it is very important that the user has an adequate attitude and financial behavior supported with skills, through this he will have vast opportunities to develop in the environment and to obtain a long term economic insurability.